Hydrogeophysical Validation of GIS-Based Groundwater Potential Mapping in Lagos Island, Nigeria - Omachoko, O. S.; Ghandi, M. D.; Edoki, I. E.; Atoki, L. O. (Journal of Spatial Information Sciences, 2026)
In rapidly urbanizing settings where public water supply systems are inadequate, stream or surface water has emerged as an important freshwater resource. The study combined the use of Geographic Information Systems (GIS), Remote Sensing (RS) and Vertical Electrical Sounding (VES) techniques to map and validate groundwater potential in Lagos Island, Nigeria. Six groundwater conditioning factors were prepared and integrated: geology, slope, rainfall, soil, drainage density, and lineament density, which were all done in a GIS environment using the Analytical Hierarchy Process (AHP) and weighted overlay analysis. To assess the subsurface aquifer conditions and to confirm the groundwater potential zones derived from GIS, Hydrogeophysical (Schlumberger electrode configuration) studies were done. The groundwater potential map produced revealed the study area to be under high, moderate and low groundwater potential with 78, 21 and 1 per cent of the area respectively. Overburden thickness, as interpreted from VES, ranged from 14 m to 46 m while the basement resistivity values were low, suggestive of fractured and water-bearing formations. A good agreement was found between the groundwater conditions obtained from the GIS-AHP results and VES results, which shows that the combination of the geospatial and the hydrogeophysical methods in groundwater exploration is reliable. The study emphasizes the benefits of hydrogeophysical validation to enhance the groundwater potential evaluation in a coastal urban setting. Recommendations for future groundwater exploration programmes include hydrogeophysical validation, groundwater monitoring systems and more field-based datasets to improve sustainable groundwater resource management in Lagos Island and other coastal urban settings.
Keywords: Hydrogeophysics; GIS; Ground water potential